Comparison between different radiological scoring systems in predicting post-PCNL outcome - N., Shaheem; Venugopalan, A. V. (International Surgery Journal, 2023)
Background: Various scoring systems, including Guy's stone score (GSS), S.T.O.N.E. score, and Clinical Research Office of the Endourological Society (CROES) nomogram, have been assessed for predicting post-percutaneous nephrolithotomy (PCNL) success in terms of stone-free status (SFS) and complications. Our study aims to determine the optimal predictor of SFS among these systems and assess their efficacy in predicting perioperative factors and complications, using modified Clavien grade. Methods: This prospective hospital-based cohort study involved 107 patients aged ≥18 years who underwent standard PCNL (tract size >24 Fr) within a year. GSS, S.T.O.N.E. score, and CROES nomogram were calculated using preoperative computed tomography (CT) scans. Comparisons between 'stone-free' and 'residual-stone' groups were statistically analyzed. Results: All parameters effectively predicted SFS. S.T.O.N.E. score exhibited excellent discriminatory power (AUC 0.844; 95% CI: 0.762-0.907), followed by GSS (AUC 0.756; 95% CI: 0.663-0.834) and CROES nomogram (AUC 0.749; 95% CI: 0.656-0.828). S.T.O.N.E. score, with an AUC of 0.844, proved the most accurate predictor at ≤7 cut-off. GUY's score correlated positively with operative time and hospital stay (correlation coefficient 0.403, 0.34). S.T.O.N.E. score also positively correlated with these factors (correlation coefficient 0.443, 0.37). CROES nomogram negatively correlated with operative time and hospital stay (correlation coefficient -0.374, -0.314). Conclusions: All scoring systems effectively predict post-PCNL SFS, with S.T.O.N.E. score being the most predictive. GSS and S.T.O.N.E. score associate significantly with operative time and hospital stay. Both GSS and S.T.O.N.E. score show significant associations with perioperative complications assessed by modified Clavien grade.